1993
DOI: 10.1088/0953-8984/5/44/019
|View full text |Cite
|
Sign up to set email alerts
|

Quantum effects in the giant magnetoresistance of magnetic multilayered structures

Abstract: We present an analytical quantum statistical theory of giant magnetoresistance in magnetic multilayers (current flowing in the plane of the layers) which takes into account both spin-dependent scattering of conduction electrons (s, d or hybridized sd electrons) and spin-dependent potential barriers between successive layers. The model also includes quantization of the momentum of conduction electrons in the direction perpendicular to the plane of the layers (kz). The influence of the following parameters is di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 29 publications
1
27
0
1
Order By: Relevance
“…This contribution originates from electron channeling as has been demonstrated within free-electron models. 114,135,136 Channeling can occur for the current parallel to the planes if a large portion of the electrons in a layer is specularly reflected from both its interfaces. If the scattering rate in that layer is lower than it is in neighboring layers, the reflected electrons in that layer see a lower effective scattering rate than they would in the absence of reflection.…”
Section: First-principle Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This contribution originates from electron channeling as has been demonstrated within free-electron models. 114,135,136 Channeling can occur for the current parallel to the planes if a large portion of the electrons in a layer is specularly reflected from both its interfaces. If the scattering rate in that layer is lower than it is in neighboring layers, the reflected electrons in that layer see a lower effective scattering rate than they would in the absence of reflection.…”
Section: First-principle Modelsmentioning
confidence: 99%
“…The effect of the intrinsic step-like potential on GMR in spin-valve structures was also considered by Vedyayev et al 136 and Barnas and Bruynseraede. 137 They found that their results are strongly influenced by quantum-size effects at small layer thicknesses and predicted oscillations in GMR as a function of the layer thicknesses.…”
mentioning
confidence: 95%
“…This potential in the hybridized band structure affects the transmission of electrons through the interface. It should be possible, therefore, for electrons to scatter specularly from such an interface, and theoretical work has predicted the effect on the transport [5][6][7][8][9][10] and coupling properties in superlattices [11][12][13].…”
mentioning
confidence: 99%
“…Си-стема уравнений (1) может быть сведена к системе обыкновенных дифференци-альных уравнений (ОДУ) с помощью преобразования Фурье по переменным x, y ( r ≡ {x, y, z}, ось z выбрана перпендикулярно границам слоев) -с помощью перехо-да к так называемому "k − z" представлению [3] -в том случае, если многослойная система однородна вдоль слоев. Уравнение (1) в этом случае принимает вид…”
Section: Introductionunclassified